Influence of Social Media on High School Students - Parian, Jerrick (Journal of Interdisciplinary Perspectives, 2025)
This quantitative study investigated the influence of social media on Grade 9 students in Veruela, Agusan del Sur, Philippines. Using a descriptive-correlational research design, the study involved a sample of early adolescent learners, many of whom were the youngest in their families and came from low-income households. Most respondents identified as Roman Catholic, with parents working primarily as farmers or homemakers. Data revealed that Facebook was the most commonly used platform, with students spending an average of 30 minutes to 3 hours daily on social media. Respondents reported using these platforms mainly for sharing and posting content, either privately or publicly. The study measured emotional influence with a mean score of 3.06 (moderately influenced) and behavioral influence with a mean score of 2.54 (influenced). A statistically significant relationship was found between students' socio-economic status and the frequency of social media usage. However, no strong associations were found between other demographic variables and social media impact. The findings suggest that excessive social media use can disrupt academic focus and classroom engagement. The study recommends increased collaboration among parents, educators, and stakeholders to foster responsible social media use and enhance students’ academic and behavioral outcomes.